Association between higher serum uric acid levels within the normal physiological range and changes of lumbar spine bone mineral density in healthy Chinese postmenopausal women: a longitudinal follow-up study. Issue 10 (October 2021) - Han, Wen; Bai, Xiaojuan; Han, Lulu; Sun, Xuefeng; Chen, Xiangmei
Abstract: Objectives: The aim of this study was to investigate whether higher serum uric acid (SUA) levels within the physiological range were associated with changes in lumbar spine bone mineral density (LBMD) in postmenopausal women without existing lumbar spine osteoporosis after a longitudinal follow-up of 3.09 years, and to further confirm the relationship between SUA and bone mineral density (BMD) in other sites such as femoral neck, total hip, and trochanter at follow-up. Methods: A longitudinal study of 175 healthy postmenopausal women without osteoporosis was conducted in Shenyang, China. BMD of the lumbar spine, femoral neck, total hip, and trochanter were measured using dual-energy x-ray absorptiometry at each visit. Pearson's correlation analysis and regression analyses were performed to determine any associations. Results: There were positive correlations between baseline SUA and BMD of the lumbar spine ( P = 0.03), total hip ( P = 0.04), and trochanter ( P = 0.04). Moreover, higher baseline SUA levels were independently associated with LBMD decline and the odds ratio of the baseline SUA of the third quartile group was 0.12 (95% confidence interval, 0.02-0.70, P < 0.05), with P = 0.23 for the trend in baseline SUA when compared with participants in the lowest, first quartile group after adjustment for many potential confounding variables. Conclusions: Higher SUA levels within the normal physiological range were independently associated with decreased LBMD, and SUA levels were positively related to the BMD of the lumbar spine, total hip, and trochanter in healthy Chinese postmenopausal women.